Szacowanie ryzyka ekstremalnego na rynku energii w Polsce - Pietrzyk, Radosław (Estimating Extreme Risk in the Polish Energy Market, 2009)
In this paper, a study on tail index estimation has been carried out. Extreme daily changes in the Polish energy market are estimated with the use of the peaks over threshold method.. The parameters of Generalized Pareto distribution are estimated with the use of maximum likelihood estimation. The peaks over threshold method provides a simple tool for estimating tail-related risk measures like Value at Risk and Expected Shortfall. This method has been verified in the Polish energy market. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 451-459